1983
DOI: 10.1139/b83-105
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of vesicular–arbuscular endomycorrhizal symbiosis

Abstract: The enhanced growth of plants infected by vesicular–arbuscular (VA) mycorrhizal fungi results primarily from improved uptake of soil phosphate. Extra phosphate reaches the root through the fungal hyphae, which tap the soluble P in soil beyond the phosphate-depletion zone near the root surface. This mechanism can explain the many corrrelations between root geometry and mycotrophy and other nutritional effects of VA mycorrhizae such as increased uptake of zinc and copper ions. Recently VA mycorrhizae have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1
15

Year Published

1987
1987
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(153 citation statements)
references
References 70 publications
8
129
1
15
Order By: Relevance
“…The results confirm that VAM associations have a marked influence on growth and nitrogen fixation of actinorhizal plants, as is also seen in legumes, especially in soils with low P availability (Smith, Nicholas & Smith, 1979;Hayman, 1983;. In this experiment VAM did not greatly improve growth in the most P-deficient soils, a result previously reported by Plenchette, Fortin & Furlan (1983) and Davis, Youngberg & Rose (1984).…”
Section: Discussionsupporting
confidence: 91%
“…The results confirm that VAM associations have a marked influence on growth and nitrogen fixation of actinorhizal plants, as is also seen in legumes, especially in soils with low P availability (Smith, Nicholas & Smith, 1979;Hayman, 1983;. In this experiment VAM did not greatly improve growth in the most P-deficient soils, a result previously reported by Plenchette, Fortin & Furlan (1983) and Davis, Youngberg & Rose (1984).…”
Section: Discussionsupporting
confidence: 91%
“…muchos autores han demostrado que las plantas micorrizadas absorben fósforo del suelo más eficientemente que las plantas no colonizadas (stribey 1987, aguirre-medina y Kohashi 2002) debido a la capacidad de las hifas para explorar mayor volumen de sustrato y con más eficiencia en comparación con un sistema radical no micorrizado (Bolan 1991). Las hifas fúngicas tienen mayor afinidad por el ion fosfato cuando su concentración es baja en la solución (Hayman 1983, gianinazzi-Pearson y gianinazzi 1986) y las raíces micorrizadas se mantienen funcionales por más tiempo (Hayman 1983).…”
Section: Contenido De Fósforo Nitrógeno Y Calciounclassified
“…This result is very interesting but the reason is not clear. However, it is usually reported that degrees of VAM colonization, and the beneficial effects associated with VAM colonization, decrease as the supply of soil P increases (Abbott and Robson 1982;Hayman 1983). Moreover, inoculation of VAM has sometimes depressed plant growth, especially when P supply is not limiting (Buwalda and Goh 1982;Hays et al 1982).…”
Section: Plant Growthmentioning
confidence: 99%